Sport and the environment : politics and preferred futures - Wilson, Brian; Millington, Brad (Bingley, U.K. : Emerald Publishing Limited, 2020)
Sport and the environment are inextricably linked. Sport is dependent on its environmental contexts and is potentially environmentally impactful in its own right. Sport facilities - like ski hills, golf courses, and stadiums - can upset ecosystems and displace local residents. Teams and fans commonly travel in cars and planes that emit CO2. Rising temperatures might make participation in some sports impossible. Other examples abound. Yet while sport can be environmentally damaging, there is also hope that it can be a force for positive environmental change - for example, in modelling pro-environment forms of sport, and in decision-making by sport's many stakeholders. In a context where pressing concerns about the climate crisis have inspired calls for changes in how people relate to the environment, questions remain about the environmental sustainability of sport. Such questions are at the core of "Sport and the environment: politics and preferred futures", which brings together a diverse collection of contributors to explore a range of topics, such as how sport is implicated in environmentally damaging activities, how decisions about responding to environmental issues are made, who benefits most and least from these decisions, and, ultimately, what a truly environmentally-friendly sport could look like.
Includes index.
Includes bibliographical references.
Print version record.
Keywords: Sports -- Environmental aspects; Sports -- Sociological aspects; Sports & Recreation -- General; Sports management & facilities